OFR-16-78 Desired Behavior Through Understanding The Federal Coal Mine Health And Safety Act Of 1969 - Charles R. Harrison (The National Institute for Occupational Safety and Health (NIOSH), 1977)
The purpose of this study and resulting development of the training program, "Safety--Let's Make It Happen" was to determine the relation of concepts to the development of desired Health and Safety behavior. After extensive pre-contract study, it was hypothesized that improved acceptance and understanding of the Federal Coal Mine Health and Safety Act of 1969 could possibly contribute to the reduction of accidents. Second, in order for an individual to accept and understand the Act, he or she must have a working knowledge of its purposes and application. Third, acceptance and understanding of the Act, necessary to protect the individual from negligence, was imperative. Fourth, an actual operating company could provide the base in which to test these hypotheses in a meaningful manner and develop this type of training program. Six assumptions were agreed upon before embarking on this study and training program development. (1) In the cognitive process, a concept introduction into an individual's personality may result in a behavior quite different than if he or she had been exposed to a different concept.